Thu hút nguồn vốn tư nhân đầu tư vào cơ sở hạ tầng: Bằng chứng thực nghiệm từ một số nước và khuyến nghị cho Việt Nam - Nguyen Thi My , Linh; Lai Cao Mai , Phuong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
By analyzing the panel data based on the Worldbank’s statistical data of the four countries including China, Thailand, and Chile from 1990 to 2014, this research reveals several factors with their influence on the decision of private investors in infrastructure investment. The results attained from empirical evidence show that net foreign direct investment funds, stock market capitalization, real interest rates, lending rates, and annual GDP growth rates have positive effects on attraction of the private participation in infrastructure development among the surveyed countries. Rooted from these results and practices of these countries, some recommendations are given with regard to the addressed issue in the context of Vietnam.